2004
DOI: 10.1200/jco.2004.08.140
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Outcome in Melanoma Patients With Cerebral Metastases

Abstract: This large series documents the characteristics of patients who developed cerebral metastases from melanoma. Median survival was dependent on treatment, which in turn was dependent on patient selection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
314
5
21

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 396 publications
(373 citation statements)
references
References 36 publications
24
314
5
21
Order By: Relevance
“…16 The reported objective response rates of symptomatic brain metastases from melanoma to WBRT range from 11% to 14%. 2,[7][8][9][10]16 These data indicate that WBRT is of little benefit in the majority of patients who have symptomatic brain metastases from melanoma. In addition, the duration of such treatment will take a substantial part of the rest of these patients lives, and its side effects, like fatigue, nausea, and hair loss, signify an additional burden for these patients.…”
Section: Toxicitymentioning
confidence: 98%
See 1 more Smart Citation
“…16 The reported objective response rates of symptomatic brain metastases from melanoma to WBRT range from 11% to 14%. 2,[7][8][9][10]16 These data indicate that WBRT is of little benefit in the majority of patients who have symptomatic brain metastases from melanoma. In addition, the duration of such treatment will take a substantial part of the rest of these patients lives, and its side effects, like fatigue, nausea, and hair loss, signify an additional burden for these patients.…”
Section: Toxicitymentioning
confidence: 98%
“…[4][5][6] The standard treatment for patients with symptomatic brain metastasis and active extracranial metastases consists of whole-brain RT (WBRT) in combination with corticosteroids that, nonetheless, is barely effective (the median survival is about 3, and most treated patients dye of neurologic disease). 1,2,[7][8][9] In fact, the objective response rate of symptomatic brain metastasis from melanoma to conventional WBRT probably is not greater than 15% 7,10 ; and, for the majority of patients, the burden of such treatment may have more negative impact on the quality of life than the doubtful benefit to survival compared with corticosteroids and other supportive measures. Data about the efficacy of RT in patients with asymptomatic brain metastasis from melanoma are lacking.…”
mentioning
confidence: 99%
“…Medications that have activity in brain metastases include the BRAF kinase inhibitors dabrafenib and vemurafenib and the MEK inhibitor trametinib. This is critical considering that median duration of survival is 4 months in patients with melanoma brain metastases in previously reported series [57]. A multicenter phase II trial of dabrafenib in patients with BRAF-mutant melanoma with brain metastases found the drug to have significant activity in the central nervous system.…”
Section: Melanoma and Immunotherapymentioning
confidence: 99%
“…In our population brain metastases were first detected by PET/CT in 2 and by MRI or CCT in 9 of 11 patients. Detecting and staging for brain metastases in melanoma patients is important for choosing individual therapy which can consist of surgery, radiotherapy or chemotherapy or combinations of these strategies (35,36).…”
Section: Fdg-pet/ct Is Increasingly Used For Therapy Assessment Of DImentioning
confidence: 99%